2016
DOI: 10.1016/j.jcrysgro.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

4H–SiC homoepitaxy on nearly on-axis substrates using TFS-towards high quality epitaxial growth

Abstract: We report high quality homoepitaxial growth on nearly on-axis () 4H-SiC substrates by chemical vapor deposition (CVD) using Tetrafluorosilane and Propane as Si and C-precursors, respectively. N-type unintentional doping (10 17 cm-3 to 10 14 cm-3) was obtained for 0.6 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…It has been shown for fluorinated CVD of SiC on on-axis 4H SiC (0001) substrates that the growth rate is limited by the amount of carbon containing species (C-limited) for higher inlet C/Si ratios. 25 We find, however, that the onset of epitaxial growth also changes with the inlet C/Si ratio as shown in Figure 2, where the onset of epitaxial growth shifts downstream in the susceptor for increased inlet C/Si ratio.…”
Section: Resultsmentioning
confidence: 69%
“…It has been shown for fluorinated CVD of SiC on on-axis 4H SiC (0001) substrates that the growth rate is limited by the amount of carbon containing species (C-limited) for higher inlet C/Si ratios. 25 We find, however, that the onset of epitaxial growth also changes with the inlet C/Si ratio as shown in Figure 2, where the onset of epitaxial growth shifts downstream in the susceptor for increased inlet C/Si ratio.…”
Section: Resultsmentioning
confidence: 69%
“…EG showed the key Raman peaks at ∼1580, ∼1350, and ∼2650 cm –1 with a D/G ratio of ∼0.1, indicating good quality. The thickness from X-ray photoelectron spectroscopy was ∼15 monolayers. , Individual circular device mesas with diameters ∼250 μm were fabricated by using standard photolithography and O 2 -plasma reactive ion etching.…”
Section: Methodsmentioning
confidence: 99%
“…The thickness from X-ray photoelectron spectroscopy was ∼15 monolayers. 26,30 Individual circular device mesas with diameters ∼250 μm were fabricated by using standard photolithography and O 2 -plasma reactive ion etching.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…For on-axis homoepitaxial growth, one of the major challenges has been to control the spontaneous formation of 3C-SiC inclusions on the Si-face of 4H-SiC substrates. It has been shown that 100% 4H polytype can be obtained in epilayers grown on the Si-face of 2-in. diameter wafers through controlling the substrate’s surface etching and early stage of the growth .…”
Section: Introductionmentioning
confidence: 99%